In vitro test for compatibility of biofertilizers containing phosphate solubilizers and nitrogen-fixing bacteria. (December 2019) - Fitriatin, B N; Nurmala, D
Abstract: The quality of biofertilizers is determined by the content of isolates and synergism between isolates. The experiment was aimed to investigate the compatibillty of biofertilizers containing P-solubilizers and N-fixing bacteria. In vitro test using isolates of PSB and N-fixing bacteria was done to study the synergystic character by using streak method on nutrient agar for the bacteria and potato dextrose agar for the fungi. Species of P-solubilizers were Pseudomonas mallei, P. cepaceae, Aspergillus niger, and Penicillium sp., and species of N-fixing bacteria were Azotobacter chroococum and Azospirillum sp. The results revealed that the P-soluilizers microbes and N-fixing bacteria were synergistic and did not antagonistic to each other. Biofertilizers which contain P-solubilizers and N-fixing bacteria can be used for agricultural purposes.